Towards multiple interactions of inner and outer sensations in corporeal awareness - Lucci, Giuliana; Pazzaglia, Mariella (Frontiers in Human Neuroscience, 2015)
Under normal circumstances, different inner- and outer-body sources are integrated to form coherent and accurate mental experiences of the state of the body, leading to the phenomenon of corporeal awareness. How these processes are affected by changes in inner and outer inputs to the body remains unclear. Here, we aim to present empirical evidence in which people with a massive sensory and motor disconnection may continue to experience feelings of general body state awareness without complete control of their inner and outer states. In these clinical populations, the activity of the neural structures subserving inner and outer body processing can be manipulated and tuned by means of body illusions that are usually based on multisensory stimulation. We suggest that a multisensory therapeutic approach could be adopted in the context of therapies for patients suffering from deafferentation and deefferentation. In this way, these individuals could regain a more complete feeling and control of the sensations they experience, which vary widely depending on their neurological condition.